PERAN KOMUNIKASI INTERPERSONAL DENGAN PASANGAN LAWAN JENIS TERHADAP MOTIVASI BELAJAR MAHASISWA - Syanah Talitha Ardelia; Alfi Rahmawati (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This research explores by the importance of interpersonal communication in romantic relationships between college students, which has the potential to influence their learning motivation. The purpose of this study is to analyze how interpersonal communication with opposite-sex partners contributes to students' learning motivation and the accompanying psychological factors. This study used a qualitative approach with descriptive methods. Data were collected through in-depth interviews with active college students who were in romantic relationships during their studies in Sukabumi City. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that interpersonal communication in romantic relationships among students tends to be flexible, open, and supported by empathy, support, and equality. Communication built from interpersonal relationships with partners acts as a support system that can increase the process of learning enthusiasm, form more regular and disciplined learning habits, and learning motivation is reinforced through joint study activities that provide discussion partners. However, conflict in relationships can cause emotional disturbances that affect a temporary decrease in learning concentration. Psychologically, interpersonal relationships have a positive impact in the form of comfort, self-confidence, and emotional balance. This study concludes that interpersonal communication with partners has a significant role in supporting students' learning motivation, with the note that communication quality and conflict management skills are the main determining factors. This research is expected to be a practical reference for students, counselors, and educational institutions on how and what the impact of managing healthy interpersonal relationships is to support students' academic success.